Critical shortage of capacity to deliver safe paediatric surgery in sub-Saharan Africa: evidence from 67 hospitals in Malawi, Zambia, and Tanzania - Jakub Gajewski; Jakub Gajewski; Chiara Pittalis; Eric Borgstein; Leon Bijlmakers; Gerald Mwapasa; Mweene Cheelo; Adinan Juma; Muskan Sardana; Ruairi Brugha (Frontiers in Pediatrics, 2023)
IntroductionPaediatric surgical care is a significant challenge in Sub-Saharan Africa (SSA), where 42% of the population are children. Building paediatric surgical capacity to meet SSA country needs is a priority. This study aimed to assess district hospital paediatric surgical capacity in three countries: Malawi, Tanzania and Zambia (MTZ).MethodsData from 67 district-level hospitals in MTZ were collected using a PediPIPES survey tool. Its five components are procedures, personnel, infrastructure, equipment, and supplies. A PediPIPES Index was calculated for each country, and a two-tailed analysis of variance test was used to explore cross-country comparisons.ResultsSimilar paediatric surgical capacity index scores and shortages were observed across countries, greater in Malawi and less in Tanzania. Almost all hospitals reported the capacity to perform common minor surgical procedures and less complex resuscitation interventions. Capacity to undertake common abdominal, orthopaedic and urogenital procedures varied—more often reported in Malawi and less often in Tanzania. There were no paediatric or general surgeons or anaesthesiologists at district hospitals. General medical officers with some training to do surgery on children were present (more often in Zambia). Paediatric surgical equipment and supplies were poor in all three countries. Malawi district hospitals had the poorest supply of electricity and water.ConclusionsWith no specialists in district hospitals in MTZ, access to safe paediatric surgery is compromised, aggravated by shortages of infrastructure, equipment and supplies. Significant investments are required to address these shortfalls. SSA countries need to define what procedures are appropriate to national, referral and district hospital levels and ensure that an appropriate paediatric surgical workforce is in place at district hospitals, trained and supervised to undertake these essential surgical procedures so as to meet population needs.